2001
DOI: 10.1002/1521-3919(20010201)10:2<108::aid-mats108>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

A Density Functional Theory (DFT) Quantum-Chemical Approach to the Real Structure of Poly(methylaluminoxane)

Abstract: DFT quantum chemical calculations have been performed in order to optimize the geometric and electronic cage structure of poly(methylaluminoxane) (MAO) with oligomerization degree n = 9–15, and to find such structures that fit most closely the existing experimental data on the MAO composition and structure. The following peculiarities of the MAO structure were found: i) In “classic” MAO (n = 9, 12, 15; Al : CH3 : O = 1 : 1 : 1), which has a triple‐layer cage structure, the inner layer contains highly reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Molecular-orbital analysis of "classic" MAO shows that the LUMO (lowest unoccupied molecular orbital) has the most contribution from the anti-bonding r*-orbitals of Al 2 1O 2 bonds. [16] Basing on the above data, it seems reasonable to suggest that the Al 2 1O 2 bond is the most reactive, and exactly this bond seems to be responsible for the formation of the Zr1O complex as a result of the reaction between "classic" MAO (AlMeO) 6 and (g 5 -C 5 H 5 ) 2 ZrMe 2 . The calculated data presented in Table 1 and Figure 1b show that the Zr1O complex represents a stable molecular compound with the length of the Zr1O bond equal to 2.15 .…”
Section: Methods and Details Of Calculationsmentioning
confidence: 79%
See 4 more Smart Citations
“…Molecular-orbital analysis of "classic" MAO shows that the LUMO (lowest unoccupied molecular orbital) has the most contribution from the anti-bonding r*-orbitals of Al 2 1O 2 bonds. [16] Basing on the above data, it seems reasonable to suggest that the Al 2 1O 2 bond is the most reactive, and exactly this bond seems to be responsible for the formation of the Zr1O complex as a result of the reaction between "classic" MAO (AlMeO) 6 and (g 5 -C 5 H 5 ) 2 ZrMe 2 . The calculated data presented in Table 1 and Figure 1b show that the Zr1O complex represents a stable molecular compound with the length of the Zr1O bond equal to 2.15 .…”
Section: Methods and Details Of Calculationsmentioning
confidence: 79%
“…[21] Models of "true" MAO structures with the composition [(AlMeO) 3m N mAlMe 3 ] (m = 2, 3, 4) have been suggested. [16] A common principle for the design of molecular MAO structures characterized by the ratio Al/ Me/O = 1 : 1.5 : 0.75 has been proposed, [13,16] in which it is suggested that the (AlMeO) 3m N mAlMe 3 structures ("true" MAO) are formed by bonding the mAlMe 3 molecules to the cage structure (AlMeO) 3m ("classic" MAO), with m = 2, 3, 4. Ziegler et al [17] have considered the different MAO cage structures with the general formula (AlMeO) n (n = 4-30).…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations